Campground or losing ground for adaptation? A case study of coastal change under neoliberal settings in New South Wales. (15th February 2023) - Leitch, Anne M.
Abstract: Coastal areas are at risk from the dual burden of climate change and rapid development. Coastal areas are significant as contested interfaces where social, cultural and environmental values vie for attention amongst economic and political aspirations. As a political logic, neoliberalism favours market-based logics, privatisations and commodification. Under neoliberal settings, planning for coastal adaptation is constantly tempered by an economic agenda. This case study analyses the management of a particular coastal land use in New South Wales, Australia following a change in management which signals a move to the market-based settings of neoliberalism. Specifically, this paper examines the case of campgrounds on public lands following a State-led change of management from local municipality to a state-run enterprise. I draw on a critical discourse analysis to study local and national media articles and coastal and campgrounds management documents. Findings highlight the influence of neoliberal settings on community consultation, local knowledge and community connections to the coast; management of coastal risks and responsibilities; and the change from nature-based holidays to a more commodified experience. Discussed is how this change and approach is likely to impact on climate change adaptation, with a call for more ambitious and inclusive conversations around coastal futures under a changing climate. Graphical abstract: Image 1 Highlights: Coastal adaptation is shaped by social processes and relies on community connection, local knowledge, values and aspirations. Campgrounds are a mainstay of coastal recreation: families return to the same spot drawn by attachment to place and community. Change in campground management from local to state-run enterprise highlights a neoliberal approach that influences adaptation. A neoliberal approach applies settings that privileges economic over social and environmental values.